Local Chromatin Features Including PU.1 and IKAROS Binding and H3K4 Methylation Shape the Repertoire of Immunoglobulin Kappa Genes Chosen for V(D)J Recombination - Matheson, Louise S.; Bolland, Daniel J.; Chovanec, Peter; Krueger, Felix; Andrews, Simon; Koohy, Hashem; Corcoran, Anne E. (Frontiers in Immunology, 2017)
V(D)J recombination is essential for the generation of diverse antigen receptor (AgR) repertoires. In B cells, immunoglobulin kappa (Igκ) light chain recombination follows immunoglobulin heavy chain (Igh) recombination. We recently developed the DNA-based VDJ-seq assay for the unbiased quantitation of Igh VH and DH repertoires. Integration of VDJ-seq data with genome-wide epigenetic datasets revealed that two chromatin states at the recombination signal sequence (RSS) of VH genes are highly predictive of recombination in mouse pro-B cells. It is unknown whether local chromatin states contribute to Vκ gene choice during Igκ recombination. Here we adapt VDJ-seq to profile the Igκ VκJκ repertoire and present a comprehensive readout in mouse pre-B cells, revealing highly variable Vκ gene usage. Integration with epigenetic datasets identified PU.1 binding at the RSS, which was unimportant for Igh, as highly predictive of whether a Vκ gene will recombine or not, suggesting that it plays a binary, all-or-nothing role, priming genes for recombination. Thereafter, the frequency with which these genes recombine was shaped both by the presence and level of enrichment of several other epigenetic features, including H3K4 methylation and IKAROS binding. Moreover, in contrast to the Igh locus, the epigenetic landscape of the promoter, as well as of the RSS, contributes to Vκ gene recombination. Thus, multiple facets of local epigenetic features explain much of the variation in Vκ gene usage. Together, these findings reveal shared and divergent epigenetic roles in AgR V(D)J recombination and provide avenues for further investigation of chromatin signatures that may underpin V(D)J-mediated chromosomal translocations.